2014
DOI: 10.22146/gamaijb.5473
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of S&P CNX Nifty Index Option of the National Stock Exchange (NSE), India, using Box Spread Arbitrage Strategy

Abstract: Box spread is a trading strategy in which one simultaneously buys and sells options having the same underlying asset and time to expiration, but different exercise prices. This study examined the efficiency of European style S&P CNX Nifty Index options of National Stock Exchange, (NSE) India by making use of high-frequency data on put and call options written on Nifty (Time-stamped transactions data) for the time period between 1 st January 2002 and 31 st December 2005 using box-spread arbitrage strategy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Čirjevskisa and Tatevosjans (2015), tested the real option in the real Estate market, in order to analysis of investment project "Sun village", during the period of 2008 to 2013 using three real option valuations methods; Tomato Garden, Black-Sholes and Binomial option pricing models, the main results which were founded by the authors are; the option to sell current project is inefficient, and the existence of the uncertainty concerning the project outcome due to high volatility level, finally both of the Black-Sholes and the Binomial model proves their efficiency to predict approximately the same result of option value. The study of Girish and Rastogi (2013), examined the efficiency of the European call/put S&P CNX Nifty index options during the period of 1/1/2002 to 31/12/2005 using high-frequency data and Box-spread strategy, the findings highlighted that the internal option market is efficient over the years for the S&P CNX Nifty index option. Black and Scholes (1973); presented a paper untitled by the pricing of options and corporate liabilities, under the principle of the options are not correctly priced in the markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Čirjevskisa and Tatevosjans (2015), tested the real option in the real Estate market, in order to analysis of investment project "Sun village", during the period of 2008 to 2013 using three real option valuations methods; Tomato Garden, Black-Sholes and Binomial option pricing models, the main results which were founded by the authors are; the option to sell current project is inefficient, and the existence of the uncertainty concerning the project outcome due to high volatility level, finally both of the Black-Sholes and the Binomial model proves their efficiency to predict approximately the same result of option value. The study of Girish and Rastogi (2013), examined the efficiency of the European call/put S&P CNX Nifty index options during the period of 1/1/2002 to 31/12/2005 using high-frequency data and Box-spread strategy, the findings highlighted that the internal option market is efficient over the years for the S&P CNX Nifty index option. Black and Scholes (1973); presented a paper untitled by the pricing of options and corporate liabilities, under the principle of the options are not correctly priced in the markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Event study techniques elucidates impact of any particular incident on the returns of stock market by designing a window both pre-event and post-event and computing abnormal returns during the period. The same technique is employed in literature for ascertaining efficiency of stock market as advocated by [4].…”
Section: Literature Review and Indian Stock Marketmentioning
confidence: 99%
“…Literature elucidates many studies exploring the impact of structural changes, political effects, dividend proclamations, oil shocks, etc. on stock market [4]. In this study the author investigates the impact of implementation of goods and services tax on national stock exchange of India by considering nifty 50 index and by applying event study technique.…”
Section: Introductionmentioning
confidence: 99%
“…The initial public offer or the fresh issue of securities takes place in primary market and trading of the issued securities among investors takes place in secondary market. In India, it has been observed that retail individual investor's participation in the primary market for equity has been massive in the last few decades and is testified by the number of companies that have been offering equity through primary markets (Girish & Rastogi, 2013). Reforms in Indian financial market such as Screen based trading, Dematerialization of shares, Setting up clearing houses, Proper guidelines and norms for settlement procedures, corporate governance standards has nearly eliminated various risks involved in trading and has motivated Foreign Institutional Investors (FIIs), Individual Retail Investors, Domestic Institutional investors to take cognizance of the highest standard of practices followed in Indian financial market and has been promoting active trading in these markets.…”
Section: Introductionmentioning
confidence: 99%